2021
DOI: 10.1002/rco2.52
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent training rejuvenates and enhances transcriptome and methylome responses in young and older human muscle

Abstract: BackgroundThe interaction between the muscle methylome and transcriptome is understudied during ageing and periods of resistance training in young, but especially older adults. More information is needed on the role of retained methylome training adaptations in muscle memory to understand muscle phenotypical and molecular restoration after inactivity or disuse. Methods We measured CpG methylation (microarray) and RNA expression (RNA sequencing) in young (n = 5; age = 22 ± 2 years) and older (n = 6; age = 65 ± … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 99 publications
2
22
0
Order By: Relevance
“…In some instances, chronological age is less associated with muscle dysfunction than other related factors such as body mass or cardiorespiratory fitness (Distefano et al, 2017 ). Nevertheless, the attenuation of muscle epigenetic aging by exercise supports recent targeted observations in humans (Blocquiaux et al, 2021 ; Ruple et al, 2021 ) and adds to the growing body of evidence touting exercise as a strategy to extend healthspan. Our work provides potentially modifiable epigenetic markers for improving muscle health with age once the mechanistic bases of dynamic DNA methylation alterations in muscle fibers are more clearly defined (Small et al, 2021 ).…”
Section: Resultssupporting
confidence: 71%
“…In some instances, chronological age is less associated with muscle dysfunction than other related factors such as body mass or cardiorespiratory fitness (Distefano et al, 2017 ). Nevertheless, the attenuation of muscle epigenetic aging by exercise supports recent targeted observations in humans (Blocquiaux et al, 2021 ; Ruple et al, 2021 ) and adds to the growing body of evidence touting exercise as a strategy to extend healthspan. Our work provides potentially modifiable epigenetic markers for improving muscle health with age once the mechanistic bases of dynamic DNA methylation alterations in muscle fibers are more clearly defined (Small et al, 2021 ).…”
Section: Resultssupporting
confidence: 71%
“…aerobic [35] vs. resistance [17,18] vs. high intensity exercise [34]) promote this hypomethylation of divergent genes and pathways. Exercise has therefore been proposed to be epigenetically 'anti-ageing' [28,29,[36][37][38][39]. Where we have also demonstrated that resistance exercise can reset the mitochondrial methylome in elderly individuals [36] and others have demonstrated this in aged humans and mice where resistance exercise and power weighted wheel running, respectively, can help return DNA methylation signatures back towards those observed in younger individuals [29,37].…”
Section: Aerobic Exercise Training In Cancer Survivors Helped 'Rejuve...mentioning
confidence: 54%
“…Indeed, work by Blocquiaux et al questioned whether increased physical activity in the form of resistance exercise could prevent age-related epigenetic changes. 33 Similar DNA methylome studies to those in young adult humans described above via training were performed, but also included cast immobilization and later retraining in older participants. The authors confirmed that aged muscle tissue was hypermethylated compared with young adult muscle at baseline and also confirmed that some genes demonstrated retained methylation signatures from earlier training into detraining and retraining, suggestive of an epigenetic memory of exercise in aged muscle.…”
Section: Exercise and Epigenetics: The Beneficial Impact On Muscle Ad...mentioning
confidence: 99%
“…They also suggested that training was able to return 73% of CpGs in aged muscle (hypermethylated) back toward levels seen in the young adults at baseline (hypomethylated), and that retraining enhanced this effect further. 33 Therefore, suggesting that exercise could rejuvenate the aged skeletal muscle methylome toward signatures observed in younger adults. Finally, we also demonstrated this rejuvenation effect of exercise on the DNA methylome in the mitochondria of aged skeletal muscle.…”
Section: Exercise and Epigenetics: The Beneficial Impact On Muscle Ad...mentioning
confidence: 99%